2022
DOI: 10.1021/acsaem.2c01965
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Hydrothermal Synthesis of Mo-Doped Ni3S2 Nanorods for Efficient Hydrogen Evolution Reaction

Abstract: In recent years, the development of catalysts for the transition-metal sulfide hydrogen evolution reaction (HER) has received extensive attention. However, the design of low-cost transition-metal sulfide-based catalysts remains a great challenge due to slow water dissociation kinetics and poor long-term stability of the catalysts during the alkaline HER. In this paper, we report the Mo-doped Ni3S2 nanorods (Mo-Ni3S2 NRs) materials prepared by a facile one-step solvothermal method. The doping of Mo accelerates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The phenomenon that electrocatalysts in situ grown or converted on the conductive substrates show enhanced HER performance has also been found in relevant reports. 43–45 The superior catalytic activity of the CoO/CC nanosheets compared to CoO (aq. )/CC further demonstrates that the interaction between the electrode materials and the substrate strongly influences the activities of the electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon that electrocatalysts in situ grown or converted on the conductive substrates show enhanced HER performance has also been found in relevant reports. 43–45 The superior catalytic activity of the CoO/CC nanosheets compared to CoO (aq. )/CC further demonstrates that the interaction between the electrode materials and the substrate strongly influences the activities of the electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…17 Lu et al reported the successful modification of the electronic structure of Ni 3 S 2 by Mo doping, accelerating the dissociation of water and improving the hydrogen adsorption capacity of Ni 3 S 2 . 18 The catalytic capability of electronically tuned catalysts is ultimately attributed to the optimized adsorption energies of the reaction intermediates. Recently, researchers have looked beyond this paradigm and noted the importance of spin polarization under a magnetic field for electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al fabricated Mo‐doped amorphous Ni 3 S 2 nanosheets, and the introduction of Mo enhanced the adsorption ability of Ni active sites to the active intermediates of HER, leading to an excellent overall water‐splitting performance 17 . Lu et al reported the successful modification of the electronic structure of Ni 3 S 2 by Mo doping, accelerating the dissociation of water and improving the hydrogen adsorption capacity of Ni 3 S 2 18 …”
Section: Introductionmentioning
confidence: 99%
“…Various types of heterostructures, nanocomposites, hybrids, different metal atoms, and single-atom dopants have been explored to modulate nanomaterials' surface morphology, chemical properties, and electronic structure. 20 Recently, graphene, reduced graphene oxide, heteroatom-doped graphene structures, and singlewalled carbon nanotubes (SWCNTs) have also emerged as an alternative because of their excellent electronic, mechanical, and chemical properties and applied to develop novel heterostructures for various applications. However, these heterostructure catalysts are costly and suffer from low electrocatalytic activities and long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have implemented different means to address the above-mentioned weaknesses and issues of metal oxide semiconductors. Various types of heterostructures, nanocomposites, hybrids, different metal atoms, and single-atom dopants have been explored to modulate nanomaterials’ surface morphology, chemical properties, and electronic structure . Recently, graphene, reduced graphene oxide, heteroatom-doped graphene structures, and single-walled carbon nanotubes (SWCNTs) have also emerged as an alternative because of their excellent electronic, mechanical, and chemical properties and applied to develop novel heterostructures for various applications.…”
Section: Introductionmentioning
confidence: 99%